Cost–benefit comparison of liraglutide and sitagliptin in the treatment of type 2 diabetes in Thailand - Chaicharn Deerochanawong (2019)
© 2019 Deerochanawong et al. Aim: Liraglutide, a once-daily subcutaneous glucagon-like peptide-1 (GLP-1) agonist, is approved for treatment of hyperglycemia in patients with type 2 diabetes mellitus (T2DM). For patients with established cardiovascular diseases, liraglutide has also been shown to reduce major cardiovascular events. However, its cost is relatively higher than other oral antidiabetic drugs. This study aims to compare the costs and benefits of liraglutide vs sitagliptin, in treating T2DM in Thailand. Methods: This study consists of two parts. In part 1, the cost of keeping T2DM under control per patient (HbA1c<7.0% with no reported hypoglycemia and no body weight gain) with liraglutide (1.2 and 1.8 mg daily) was compared with using sitagliptin (100 mg daily). Costs were based on Thai local data. Clinical outcomes were based on head-to-head randomized controlled trials. Part 2 estimated the cost-per-controlled patient, based on major cardiovascular outcomes (cardiovascular death, nonfatal myocardial infarction, nonfatal stroke). Economic benefit was calculated as the reduction in cardiovascular outcomes. Results: In Thailand, liraglutide (1.8 mg daily) costs 7.37-times more than sitagliptin 100 mg. The cost per patient achieving a composite clinical endpoint (HbA1c<7.0%, with no weight gain and no hypoglycemic events) in patients with T2DM receiving liraglutide 1.8 mg is 2.80-times higher than patients receiving sitagliptin 100 mg. When cardiovascular benefits (reduced composite endpoint of major cardiovascular events, ie, cardiovascular death, nonfatal myocardial infarction, and nonfatal stroke) were taken into account, it was found that liraglutide had lower cost than sitagliptin, resulting in estimated savings of 20,085 THB (620 USD) per patient per year. Conclusion: The clinical benefits of liraglutide (HbA1c<7.0%, no hypoglycemia, no weight gain, reduced cardiovascular outcomes) partly offset its high price. Therefore, liraglutide should be considered as an appropriate treatment alternative to sitagliptin, particularly for T2DM patients with high cardiovascular risks.